2012
DOI: 10.3402/ehtj.v5i0.7270
|View full text |Cite
|
Sign up to set email alerts
|

Optimism of health care workers during a disaster: a review of the literature

Abstract: Optimism has several orientations. One such outlook is a general tendency to regard the world as a positive place, accepting difficulties as mere challenges instead of impassable barriers. Among health care workers, optimism improves their level of functioning, their patients’ satisfaction, and their therapeutic results. Optimistic staff members report feeling less pressure, use fewer avoidance strategies, focus on practical problem solutions, seek social support, and have more trust in people and organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 23 publications
(29 reference statements)
1
27
0
1
Order By: Relevance
“…According to a study by Ingledew and Brunning (1999) , preventive health behavior has a positive effect on comparative optimism. Furthermore, optimism is also revealed to be one of the key components of resilience ( Boldor et al., 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to a study by Ingledew and Brunning (1999) , preventive health behavior has a positive effect on comparative optimism. Furthermore, optimism is also revealed to be one of the key components of resilience ( Boldor et al., 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Green et al (2010) found that veterans with higher resilience were less likely to develop depressive symptomology, even after controlling for age, gender, minority status, trauma exposure, and PTSD diagnosis. Proposed explanations were that resilient individuals were confident of their personal strengths in the face of misfortune ( Pyszczynski et al, 2004 ), employed effective coping to reduce distress ( Rajkumar et al, 2008 ), used positive affect to bounce back from stressors ( Tugade and Fredrickson, 2004 ), used positive thinking to reappraise their loss ( Shiota and Levenson, 2012 ), and established hope and optimism for the future ( Boldor et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…This element can maximize the individual's ability to take care of himself or herself and people around him or her (Benedek et al, 2007 ). Self-efficacy has been widely used in mental health promotion intervention in different cultural contexts for various populations (Mueller et al, 2011 ; Boldor et al, 2012 ; Barry et al, 2013 ), but few studies have empirically tested whether the alteration effected as a result of the intervention explains the variability in the intervention outcome. In addition, goal setting, an integral manifestation of resilience, comprises of positive transformation in new opportunities and focuses on enactment of hope about a better future (Stajduhar et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%